Advances in clinical social work practice : selected papers - Germain, Carel B. (Mary Land : National Association of Social Workers, 1985)
This volume, then, exemplifies the efforts of clinical social workers to create a vital presence for clinical practice in the world of the 80s through advances in practice, advances in service provision, and advances in theory, ethics, and evaluative research.
Part I. Advances in practice -- Part II. Advances in service provision -- Part III. Advanced in theory, ethics, and evaluative research.
Keywords: SOCIAL SERVICE -- CONGRESSES; SOCIAL CASE WORK -- COGRESSES